Hubungan Konsumsi Vitamin C Dengan Kesegaran Jasmani Pada Atlet Sepakbola di Pusat Pendidikan dan Latihan Olahraga Pelajar Jawa Tengah - Nur Halimah; Ali Rosidi; Yuliana Noor SU (Jurnal Gizi, 2014)
Football athletes need a heart-lung endurance which describes the capacity to perform activities continuously for long periods without experience significant fatigue. Fulfillment of nutrients, especially vitamin was important to meet the physical needs for activities in their daily lives. One effort to get a good freshness  good nutritional status and adequacy of the proper nutrients. Lack of vitamin C can lead to lower body resistance weakened muscle contraction and fatigue. Symptoms of vitamin C deficiency is characterized by deterioration of physical appearance. The purpose of this study was to determine the relationship of vitamin C intake with physical fitness in football athletes in Sports Training and Education Center of CentralJava. Population of this study is all football athletes as many as 35 people. All of they were investigated. The data of vitamin C intake was measured by the method of weighing and 2 days food recall Physical fitness was measured by the method of the Asian Committee on the Standardization of Pysicial Fitness Test (ACSPFT). The Kolmogorov –Smirnov test was used to test the normally distribution of the data and the Pearson or Rank Spearman corelation test was used to analysis the correlation between the vitamin C intake and physical fitness level score. The results showed that the average of vitamin C intake is 83.84 mg. All of  football athletes consume the sufficient levels of vitamin C (100% and up of RDA. The average of football athelete’s physical fitness level score is 446.6 65.7% (excellent). The Kolmogorov-Smirnov test showed that yhe data of vitamin C intake and physical fitness score no normally distribution. By using the Rank-Spearman correlation test,  there is no correlation between the vitamin C intake and the physical fitness level of the  PLPP football athletes. In Central Java Sports Training and Education Center Student the football athlete’s  Vitamin C consumption level is normal and the  physical fitness categories is excellent. There is no correlation. between the vitamin C intake  and the physical fitness level of the  PLPP football athletes.